DISSECTING THE JAPANESE WAR : a study on Japanese war narratives within the Singapore landscape - Deng, Joanne (2018)
This thesis seeks to look at the way the war in Singapore is being presented through analysing the various narratives that can be found in the Singapore landscape. Categorized into three groups: National, Transnational and Sub-national, it will trace the genesis of the narrative, and study how these narratives are propagated and injected into the landscape. Furthermore, it will explain how these narratives classify the different groups of the war as “local” or “external” respectively, and how the various groups move fluidly between these classifications. Finally, it will justify how then these classifications change the individual’s perspective of a “Singaporean war” vis-à-vis “a war fought in Singapore.” Hence, this thesis will study the complexity of the war narrative in Singapore and showcase how encountering of the various narrative will shape and mould a person’s understanding of the war, making them view it as either a “Singaporean war” or “a war fought in Singapore.”